PELAKSANAAN FUNGSI MANAJEMEN PERKANTORAN POAC (PLANNING, ORGANIZING, ACTUATING, CONTROLLING) UNTUK MENINGKATKAN EFEKTIVITAS KERJA PADA BAGIAN TEKNIK DI PT PLN (PERSERO) ULP RAYON BANGIL - Susilowati Susilowati; Rossy Septyaningrum (Jurnal VOK@SINDO, 2020)
Abstract: Office management is a form of collaboration carried out in the office to achieve company goals. The form of cooperation is in the form of a series of planning, organizing, directing and monitoring (POAC) activities or called the management function. Office management affects the achievement of company goals. This study aims to determine the implementation of the management functions of the office planning, organizing, actuating, controlling (POAC) at PT PLN (Persero) ULP Rayon Bangil. This research is a type of qualitative research using descriptive research methods that are analyzing data by describing or describing data that has been collected. Data collection in this study researchers used interview and observation methods.The results of the discussion explained the implementation of the planning, organizing, directing and supervision management functions at PT PLN (Persero) ULP Rayon Bangil. Impact of management functions on office work, as well as efforts to carry out management functions in every aspect of work